Concepts and Reality in the History of Philosophy : Tracing a Philosophical Error from Locke to Bradley. - Ellis, Fiona (Taylor & Francis, 2005)
This book traces a misunderstanding about the relation of concepts and reality in the history of philosophy and proposes a Hegelian-based solution.